Daya Ovisidal dan Larvisidal Infusa Daun Bambu Apus (Gigantochloa apus)Terhadap Haemonchus Contortus Secara in Vitro - Budi Purwo Widiarso; Wisnu Nurcahyo; Kurniasih Kurniasih; Joko Prastowo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Gastrointestinal Nematodes are one among cause decrease production efificiency in goat and sheep in Indonesia, especially parasite of abomasum namely Haemonchus contortus. This parasite causes disease of Haemonchosis causing anemia, and causes mortality to young goat or sheep. Loss of economics caused by high morbidity and mortality this parasite so that can improve the expense of prevention and medication of this disease. This research aim was to evaluate ovicidal and larvicidal apus bamboo leaf infusion (Gigantochloa apus) against Haemonchus contortus by in vitro. Examination of apus bamboo leaves infusion to seven concentrations namely : 1.2; 1.0; 0.8,; 0.6; 0.4; 0.2;0.1; 0.05 and 0 mg / ml as negative control. Positive control uses Albendazole with concentration 0,025 mg / ml. The highest concentration 1.2 mg / ml apus bamboo leaves infusion inhibited 92.35% egg hatching ( LC 0.49 mg / ml ) and have larvicidal activity equal to 90% ( LC50 0,47mg / ml). The concentration 1.2 mg / ml also have similar effect with positive control which use Albendazole. Phytochemical apus bamboo leaf analysis of the highest concentration revealed the presence tanin condensed, saponins, and alkaloids.